THE IDENTITY OF HORNERA Jungh. (Thymeleaceae) - A. J. G. H. KOSTERMANS (Research Center for Biology, 1965)
Dr. Airy Shaw (Van Steenis, Fl. Males. Ser. I, 6(1): 48. 1960),referred Hornera Jungh.(Tijdschr. natuurl. Geschied. & Physiol. 7: 314. 1840) ten-tatively to Lauraceae.Hornera was described in an article with the misleading title: Nova genera et species plantarum Javanicum, as the species numbered 22 to 27 are from Japan. Under no. 22 there is a remark: